Engaging All Mathematical Learners Through Project-Based Design - Brown, Judy; Walls, Jennifer; Leis, Heather; Farrell, Ann; Meadows, Michelle; Caniglia, Joanne (Ohio Journal of School Mathematics, 2022)
The authors describe a project-based activity using TI calculators or Desmos within a high school mathematics classroom. As students learn about functions with technology using a project-based approach, they make connections between school mathematics and topics of personal interest.